PERILAKU KEPEMIMPINAN KEPALA SEKOLAH SD INPRES BERTINGKAT MAMAJANG III KOTA MAKASSAR - Hasrawati Haruna; Nur Aslindawati; Sulfaidah Sulfaidah; Erni Rismawanti; Muhammad Fahreza W (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to 1) determine the leadership behavior of the principal in providing performance guidance, 2) determine the leadership behavior of the principal in providing motivation, 3) determine the behavior of the principal in providing work productivity monitoring. This research is a qualitative research conducted at SD Inpres Mamajang III level with the research subject is the principal. Data was collected by using in-depth interviews, observation, and documentation techniques. The data analysis technique uses descriptive analysis techniques through data reduction, data display and data verification, while the validity of the data uses credibility, time triangulation, transperability, dependability, confirmability. The results of the research obtained are that the principal's leadership emphasizes three things, namely policy, motivation and monitoring. Policy is carried out by prioritizing deliberation. Motivation is done by giving awards and providing a conducive room to work. Principal monitoring uses the instrument of meeting results and the results of input from school officials